2022
DOI: 10.1038/s41598-022-07158-8
|View full text |Cite
|
Sign up to set email alerts
|

Transposase-CRISPR mediated targeted integration (TransCRISTI) in the human genome

Abstract: Various methods have been used in targeted gene knock-in applications. CRISPR-based knock-in strategies based on homology-independent repair pathways such as CRISPR HITI have been shown to possess the best efficiency for gene knock-in in mammalian cells. However, these methods suffer from the probability of plasmid backbone insertion at the target site. On the other hand, studies trying to combine the targeting ability of the Cas9 molecule and the excision/integration capacity of the PB transposase have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has been reported that PBase mutants showing higher transposase activity compared with hyPBase were developed using a screening system in yeast and applied to mammalian cells (Wen et al 2020). Furthermore, the fusion of PBase and TALE or CRISPR/Cas9 has been reported to enable the targeted integration and high-efficiency knock-in into a target gene in mammalian cells (Owens et al 2013;Rezazade Bazaz et al 2022). Recently, in mammalian cells, especially in hard-to-transfect cells like human iPSC, the piggyBac-mediated transgenesis system has made it possible to provide an effective gene correction approach using Prime Editor, which enables precise gene editing with the reverse transcription (Eggenschwiler et al 2021;Wolff et al 2021).…”
Section: Prospects For Further Improvement Of Genetic Engineering Wit...mentioning
confidence: 99%
“…It has been reported that PBase mutants showing higher transposase activity compared with hyPBase were developed using a screening system in yeast and applied to mammalian cells (Wen et al 2020). Furthermore, the fusion of PBase and TALE or CRISPR/Cas9 has been reported to enable the targeted integration and high-efficiency knock-in into a target gene in mammalian cells (Owens et al 2013;Rezazade Bazaz et al 2022). Recently, in mammalian cells, especially in hard-to-transfect cells like human iPSC, the piggyBac-mediated transgenesis system has made it possible to provide an effective gene correction approach using Prime Editor, which enables precise gene editing with the reverse transcription (Eggenschwiler et al 2021;Wolff et al 2021).…”
Section: Prospects For Further Improvement Of Genetic Engineering Wit...mentioning
confidence: 99%
“…For making our method the more universal and as efficient as possible we decided to rely on NHEJ-repair mechanisms and to involve the powerful and underrated Homology-Independent Targeted Insertion (HITI) 27 . Indeed, HITI has been reported to be the most efficient strategy to mediate knock-ins 27,44 . In addition, and in contrast to low efficiency HDR, HITI was shown to occur at every stage of cellular life, rendering our method applicable into dividing and non-dividing cells.…”
Section: Introductionmentioning
confidence: 99%